Strategi Badan Narkotika Nasional Provinsi Jawa Timur dalam Mencegah Penyalahgunaan Narkotika di Lingkup Pelajar dan Mahasiswa Melalui Program P4GN - Aulia, Defanni Nur; Ismail, Ismail; Nurany, Fierda (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Narcotics cause a downward effect to loss of consciousness, hallucinations,Â and excitability. The turn of the globalization era has an impact on the younger generation among students and students who fall into promiscuity, and what's worse is the abuse of narcotics. Therefore, how is the strategy carried out by BNN East Java Province with the stages of implementing the strategy to determine the success of a strategy. This study uses Qualitative Research Methods, is research with the intention of interpreting the phenomena that occur. In qualitative research the methods usually used are interviews and documentation. The researcher processes it by describing the data obtained in the field in the form of written or oral data from the people involved in this research. There are 4 strategies implemented by BNN East Java Province, namely, Soft Power Approach, Hard Power Approach, Smart Power Approach and Cooperation. Of the four strategic points implemented by BNN East Java Province, the researcher took the Soft Power Approach point. East Java's efforts to prevent drug abuse in the scope of students and students are by implementing the Soft Power Approach strategy, namely by providing outreach and providing motivation, as explained above, the BNN of East Java Province guides Counseling Teachers and P4GN Activists in UKM Universities and also students and students, directing the dangers of narcotics and also the efforts made by the BNN of East Java Province in order to make students and students anti-drugs.